TRANSFORMATION OF DIGITAL ZAKAT AND WAKAF: A SYSTEMATIC REVIEW OF INNOVATION MODELS - Cholid Fadil (Islamic Studies Journal (ISLAM), 2026)
The global Islamic philanthropy landscape is undergoing a fundamental paradigm shift due to massive digital disruption, transforming traditional zakat and waqf management into integrated, data-driven systems. Despite the vast potential of zakat and waqf, the realization in Indonesia remains below 7% for zakat and 1% for cash waqf, indicating a systemic failure to convert this potential into tangible economic impact. Using a systematic narrative review of literature from Scopus, Web of Science, and Google Scholar databases for the 2014-2024 period, this study synthesizes digital innovation models within a "Digital Shariah Governance" (DSG) framework. Findings indicate that the integration of blockchain technology, smart contracts, and artificial intelligence (AI) can automate Shariah compliance and ensure radical transparency through immutable and traceable transaction records. This transformation not only enhances operational efficiency but also strengthens religious legitimacy through integrated digital audit mechanisms, ultimately mitigating the public trust deficit within the Islamic social finance ecosystem.